Haemato-Biochemical Alterations After Epidural Administration of Dexmedetomidine Alone and in Combination with Bupivacaine in Buffalo Calves - Jaiswal, A.; Pandey, S.S.; Parihar, A.S.; Rajput , N.; Jain , R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was conducted on 12 healthy male buffalo calves weighing between 50 to 60 Kg to evaluate haemato-biochemical alterations after epidural injection of dexmedetomidine alone and in combination with bupivacaine. Haematological examination showed nonsignificant alterations. Biochemical examination showed significant increase in blood glucose, blood urea nitrogen and serum creatinine while there was nonsignificant alterations in total protein and alkaline phosphatase. All haemato-biochemical changes were transient and compensatory.